Agroecology versus alternative concepts - Dickens, Chris; Staiger Rivas, Simone (CGIAR System Organization, 2022)
A comprehensive undertaking on agroecology as a CGIAR initiative requires a deliberate capacity strengthening effort for its more than 100 collaborating researchers from eight CGIAR centers together with CIFOR – ICRAF, and CIRAD along with partners in seven countries: Burkina Faso, India, Kenya, Laos, Peru, Tunisia, and Zimbabwe. Indeed, the initiative unites members of different organizations in each of its five research themes so that it has become a priority to provide opportunities to expand and share the knowledge on agroecology among the team and beyond. “This space is designed to tackle core scientific topics with global relevance across countries and research themes related to the design and implementation of the CGIAR Initiative on Agroecology, be they concepts, approaches or methods,” says Bernard Triomphe, a researcher and expert in participatory innovation development from CIRAD. Triomphe, who initially suggested the seminar series, is the leader of Work Package 1 of the Initiative which focuses on the transdisciplinary co-creation of innovations in Agroecological Living Landscapes (ALLs) to test and understand the benefits of agroecological approaches.